Proteogenomics - Végvári, Ákos [Editor] (Advances in experimental medicine and biology, v. 926., 2016)
"This book highlights key technologies and identifies areas for further development in proteogenomics. The utility and usefulness of very large Omics data sets (Next Gen Sequencing of DNA, RNA-seq, ribosome profiling, mass spectrometry- and antibody-based proteomics) is discussed and opportunities and challenges of related bioinformatics applications are outlined. The reader will be able to appreciate the interdisciplinary nature of the continuously evolving area of proteogenomics, which has already grown beyond its original concept of verifying gene annotations by proteomics. The chapters presented in this book are arranged to offer a general overview, rather than to provide detailed descriptions of technologies. The selected applications will provide useful insight into the level of detail that can be obtained in relation to certain diseases areas, including cancer biology and personalized medicine. The readers will find that each chapter delivers a comprehensive approach to proteogenomics, each from the point of view of a specific application"--Publisher's description.